Investigation Science Process Skills Among Chemistry Education Student Through the Law of Mass Conversation Experiment - Nur'aini; Enawaty, Eny; Erlina (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Science process skills (SPS) are important skills that students need to master through practical activities. The purpose of this study was to identify students' SPS in the aspects of observing, classifying, interpreting, using tools and materials, and communicating in practical activities related to the law of conservation of mass. This study employed a descriptive quantitative method with 30 chemistry education students from the Faculty of Teacher Training and Education, Tanjungpura University, as the research subjects. Data were collected through observation and documentation in the form of laboratory reports. The research instrument was an observation sheet. Data was collected through observation and documentation in the form of laboratory reports. The science process skills observation sheet was validated by two experts, showing a validity value of 0.91, which falls into the very high category. The research data was analyzed quantitatively. The research results showed that the average percentage obtained for each KPS indicator for students in the observation aspect reached 87% (very good), classification 83% (very good), interpretation 69% (good), use of tools/materials 83% (very good), and communication aspect 79% (good). Overall, the average percentage of SPS based on student observation was 80% with a good category. Thus, chemistry education students have the ability to conduct scientific investigations, which is an important foundation for prospective chemistry teachers.